Controlling of Magnetic Levitation System using a Fuzzy system for tuning the PID Parameters (Al-Mansour Journal, 2022)
Magnetic levitation is an unstable and non-linear system. The main problem for these types of systems is how to develop a control system to obtain the desired output response. For years several techniques and methods have been followed to get a control system that meets requirements of stable performance. In this paper, a classical PID controller is implemented, to control a magnetic levitation system. A fuzzy system is used to modify the parameters of PID controller according to body position. The impact of system’s non-linearity has been reduced with the suggested controller. The simulation results explain that the supervisory fuzzy-PID controller has a good robustness and a quality controller. The model of the system is simulated using Matlab R (2015) a Simulink.
Keywords: Magnetic levitation system; PID controller; Fuzzy control; and Matlab Simulink